PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI WARUNG MIE AYAM BAKSO AJENG KARANGANYAR - Retno Susanti, Baron Himawan, Sumaryanto & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The purpose of this study are: 1) To analyze the significance of the influence of product quality, service quality and location of the purchase decisions of consumers in Warung Mie Ayam Bakso Ajeng Karanganyar. 2) To analyze the dominant variable influence (product quality, service quality or location) on consumer purchasing decisions in Warung Mie Ayam Bakso Ajeng Karanganyar. The research method used survey method, the type of data used quantitative and qualitative data, the data source used primary data and secondary data. The population in this study is consumers who buy at Warung Mie Ayam Bakso Ajeng Karanganyar in the period of August 2016. The number of samples in this study of 100 respondents, the sampling technique uses accidental sampling. Data collection methods used: questionnaire, observation and documentation. Data analysis technique used to test the validity, reliability test, classic assumption test, multiple linear regression analysis. Based on the results obtained conclusions: 1) There is significant influence product quality on consumer purchasing decisions in Warung Mie Ayam Bakso Ajeng Karanganyar. 2) There is significant influence of service quality to consumer purchase decisions in Warung Mie Ayam Bakso Ajeng Karanganyar. 3) There is significant influence on consumer purchasing decisions locations in Warung Mie Ayam Bakso Ajeng Karanganyar. 4) Quality of care is the dominant variable influence on consumer purchase decisions in Warung Mie Ayam Bakso Ajeng Karanganyar.Keywords: product quality, service quality, location, purchasing decisions